Does performance related pay for teachers improve student performance? Some evidence from India - Geeta Kingdon and Francis Teal (GPRG-WPS-014, 2005)
In this paper data from a school survey in India is used to ask whether there is evidence for the payment of performance related pay and whether such pay structures do impact on student achievement. It is shown that - after controlling for student ability, parental background and the resources available - private schools get significantly better academic results by relating pay to achievement; government schools do not. We discuss possible interpretations of this result.